Pembrolizumab- induced subacute cutaneous lupus erythematosus in a patient with oropharyngeal squamous cell carcinoma: A case report and literature review - Beata Mayer; Pavel Babál; Lucia Krivošíková (Human Vaccines & Immunotherapeutics)
Considering the increasing use of immune checkpoint inhibitors in cancer treatment, our aim is to report a rare cutaneous immune-related adverse event induced by PD-1 inhibitor pembrolizumab and provide a brief overview of pembrolizumab-induced subacute cutaneous lupus erythematosus (SCLE) cases in the literature. We report a 67-year-old woman with oropharyngeal squamous cell carcinoma who developed SCLE during treatment with pembrolizumab. After 18 weeks (sixth cycle) of pembrolizumab immunotherapy, a widespread pruritic erythematous rash evaluated as grade 3 immune-related adverse event appeared primarily on the patient's limbs. Histopathological examination and direct immunofluorescence showed characteristic features of SCLE. The patient was treated with oral prednisone 40 mg daily and topical corticosteroids. In 2 weeks, her rash had cleared up significantly and her pruritus had disappeared. SCLE is an infrequent but recognized immune-related adverse event linked to pembrolizumab treatment.